The Effect Of Motivation And Emotional Intelligence On Kinemployee Work In Central Tapanuli District Government - Tanjung, Mansur; of Fortune Ananda lubis , Dawn (Publisher Cv. Inara, 2022)
This study aims to determine the effect of motivation and emotional intelligence on employee performance in the government of Central Tapanuli Regency. The number of samples in this study was 146. Data collection was carried out using a questionnaire under the indicators of each variable used. The data obtained were then analyzed using multiple linear regression analysis. The results showed that motivation and emotional intelligence simultaneously has a significant effect on the performance of employees in the Government of Central Tapanuli Regency. The results of the t-test show that motivation and emotional intelligence significantly influence employee performance. The emotional intelligence factor has a more dominant influence on employee performance compared to motivation.